THE INFLUENCE OF BRANCHLESS BANKING AGENT MARKETING STRATEGY ON CUSTOMER INTEREST THROUGH SERVICE QUALITY - Akhmad Helmie Aditya; Joko Utomo; Supriyono Supriyono (JURNAL PROFIT, 2025)
This study analyzes the influence of agent marketing strategiesbranchless banking on customer interest through the service quality of PT. Bank Mandiri (Persero) Tbk Area Kudus. The results show the influence of agent marketing strategies.branchless banking on the interest of customers of PT. Bank Mandiri (Persero) Tbk vKudus, this is proven by the t valuecount amounting to 3,192 > ttableof 1.655 with a significance level below 5%. The influence of the agent's marketing strategybranchless banking regarding the quality of service of PT. Bank Mandiri (Persero) Tbk Area Kudus, this is proven by the t valuecount amounting to 2,824 > ttableof 1.655 with a significance level below 5%. The influence of customer interest on the service quality of PT. Bank Mandiri (Persero) Tbk in the Area Kudus is proven by the t-valuecount amounting to 1,819 > ttableof 1.655 with a significance level below 5%. The influence of the agent's marketing strategybranchless bankingtowards customer interest through the quality of service of PT. Bank Mandiri (Persero) Tbk Area Kudus, this is proven by the F valuecount > Ftable.This can be seen from the F value.count of 8.227 > Ftableof 3.91 with a significance level below 5%